Stock Market Participation Puzzle in Emerging Economies: the Case of Lithuania - Mauricas, Žygimantas; Darškuvienė, Valdonė; Mariničevaitė, Tamara (Organizations and Markets in Emerging Economies, 2017)
We examine underlying factors that explain an exceptionally low stock market participation rate among Lithuanian households by carrying out a comprehensive survey of mass affluent individuals. The probit regression analysis of the survey results indicates that lack of financial literacy, low risk tolerance and lack of trust in financial institutions are the three key factors explaining the stock market participation puzzle in Lithuania, while high investment fees, high stock market return expectations or underdeveloped local capital markets do not have a significant effect. The paper also examines whether the same factors also have influence on investment fund, bond and real estate market participation rates. Interestingly, lack of financial literacy, low risk tolerance, lack of trust in financial institutions and high stock market return expectations increase household participation rate in real estate market. The latter finding should be of particular interest to macro-prudential policy makers as increasing financial literacy of households and increasing trust in financial intermediaries would likely cause higher stock market participation at the expense of investments in local real estate market thus not only improving household portfolio diversification and liquidity, but also potentially mitigating local real estate boom and bust cycles.
Keywords: stock market participation puzzle; trust; financial literacy; risk tolerance; real estate